Allosteric inhibition of HSP70 in collaboration with STUB1 augments enzalutamide efficacy in antiandrogen resistant prostate tumor and patient-derived models. (March 2023) - Xu, Pengfei; Yang, Joy C.; Ning, Shu; Chen, Bo; Nip, Christopher; Wei, Qiang; Liu, Liangren; Johnson, Oleta T.; Gao, Allen C.; Gestwicki, Jason E.; Evans, Christopher P.; Liu, Chengfei
Abstract: Ubiquitin proteasome activity is suppressed in enzalutamide resistant prostate cancer cells, and the heat shock protein 70/STIP1 homology and U-box-containing protein 1 (HSP70/STUB1) machinery are involved in androgen receptor (AR) and AR variant protein stabilization. Targeting HSP70 could be a viable strategy to overcome resistance to androgen receptor signaling inhibitor (ARSI) in advanced prostate cancer. Here, we showed that a novel HSP70 allosteric inhibitor, JG98, significantly suppressed drug-resistant C4–2B MDVR and CWR22Rv1 cell growth, and enhanced enzalutamide treatment. JG98 also suppressed cell growth in conditional reprogramed cell cultures (CRCs) and organoids derived from advanced prostate cancer patient samples. Mechanistically, JG98 degraded AR/AR-V7 expression in resistant cells and promoted STUB1 nuclear translocation to bind AR-V7. Knockdown of the E3 ligase STUB1 significantly diminished the anticancer effects and partially restored AR-V7 inhibitory effects of JG98. JG231, a more potent analog developed from JG98, effectively suppressed the growth of the drug-resistant prostate cancer cells, CRCs, and organoids. Notably, the combination of JG231 and enzalutamide synergistically inhibited AR/AR-V7 expression and suppressed CWR22Rv1 xenograft tumor growth. Inhibition of HSP70 using novel small-molecule inhibitors coordinates with STUB1 to regulate AR/AR-V7 protein stabilization and ARSI resistance. Graphical Abstract: *CRPC: castration-resistant prostate cancer; PDX: patient derived xenograft; CRC: conditional reprogrammed cultures; AR-FL: full length androgen receptor; ARSI: androgen receptor signaling inhibitor. ga1 Highlights: Novel HSP70 inhibitors improve enzalutamide treatment in prostate cancer. JG98 and JG231 degrade AR-V7 in enzalutamide resistant prostate cancer cell. JG98 coordinates with STUB1 to regulate AR-V7 protein turnover. JG98 and JG231 suppress cell proliferation in clinically relevant prostate cancer models.